TOPOLOGICAL MODELLING OF THE ENERGETIC SPACE OF THE CHECHEN REPUBLIC - Zairbeg Ataev (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2014)
The article is devoted to the geographical aspects of diversity in the energy space of the Chechen Republic. The author has conducted the review of the territorial organization, identified the main problems and marked the preconditions of development. The methodology of geographical study of the diversity of regional energy space is presented in the paper. As further research directions of topology of the energy space of the Chechen Republic, it is important to identify conjugation areas of ecological, socio-economic and technological feasibility of the local power industry development, especially in the rural and mountainous areas. In the language of economic geography, it is required to perform social and electric power zoning of the region.